Konsep Dzikir dalam Tafsir Sufi Muhyiddin Ibn ‘Arabi: Kajian Tafsir Tematik terhadap Ayat-ayat Dzikir dalam al-Qur’an - Ella Safira Rahmania; Ziyad Ulhaq; Abdullah Safei (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to examine the concept of dhikr (remembrance of God) within the framework of Sufi exegesis as articulated by Ibn Arabi and to explore its relevance in contemporary life, particularly in relation to mental health and ethical formation. The background of this research is rooted in the increasing prevalence of mental health issues, which calls for an integrative approach between spirituality and modern scientific perspectives. This study employs a qualitative approach with a library research design, using primary sources from Ibn Arabi’s works, such as Tafsir al-Qur’an al-Karim and Al-Futuhat al-Makkiyah. The data are analyzed using content analysis within the framework of Sufi exegesis. The findings reveal that dhikr, in Ibn Arabi’s perspective, is not merely a verbal practice but an integral spiritual process involving inner awareness, intentionality, and an existential relationship between the servant and God. Dhikr operates in a dialogical and reciprocal manner through the mechanism of tajallī (divine self-disclosure) and encompasses both ontological and epistemological dimensions, functioning as a means of divine participation and spiritual unveiling (kashf). The centrality of ism Allāh serves as a medium of comprehensive monotheistic awareness that leads humans toward the state of insān kāmil (the perfect human). However, this study also finds that Ibn Arabi’s Sufi interpretive approach, which relies heavily on inner experience, tends to overlook the outward (ẓāhir) meaning of the text, thereby raising concerns about interpretive subjectivity. This study contributes to the development of Qur’anic studies by strengthening Sufi exegetical approaches integrated with psychospiritual perspectives. It also highlights the practical relevance of dhikr as a means of self-purification (tazkiyat al-nafs), ethical reinforcement, and a therapeutic instrument for addressing mental health challenges in contemporary society.